2008
DOI: 10.1590/s0037-86822008000100012
|View full text |Cite
|
Sign up to set email alerts
|

Manifestações otoneurológicas associadas à terapia anti-retroviral

Abstract: A associação entre a infecção pelo vírus da imunodeficiência humana (HIV) e sinais e sintomas otoneurológicos (perda de audição, zumbido e tontura) tem se tornado objeto de estudos nacionais e internacionais 2 5 7 12 30 .As causas das alterações otoneurológicas vêm sendo associadas às infecções oportunistas, às drogas ototóxicas e à ação direta vírus no sistema cocleovestibular 1 2 5 6 7 12 30 . No grupo tratado, três (1,8%) casos de perda auditiva idiopática e dois (1,3%) de perda auditiva relacionada a otosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 16 publications
0
15
1
4
Order By: Relevance
“…The obtained results confirmed one study in which the author, to characterize the results of audiologic assessment in children and adults with HIV/AIDS, observed higher occurrence of conductive hearing loss in children (92.9% of the cases), whereas in the adult population there was higher occurrence of sensorineural hearing loss (44.4% of the cases) (26) . Upon comparing the subjects with HIV/AIDS submitted and not submitted to antiretroviral therapy, the data observed in the present study showed that there were no differences in occurrence of hearing loss in these two groups, confirming the results of some specific studies in the area (14,19,20) , and disagreeing with other studies that correlated the use of antiretroviral medication with higher occurrence of hearing impairment (5,9,(15)(16)(17)(18)21) . Considering the data found in the present study, we could observe that sensorineural hearing loss was associated with the presence of HIV virus and its adverse effects in the infected subject, in agreement with other studies published in the literature (10)(11)(12)14,24,25) .…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…The obtained results confirmed one study in which the author, to characterize the results of audiologic assessment in children and adults with HIV/AIDS, observed higher occurrence of conductive hearing loss in children (92.9% of the cases), whereas in the adult population there was higher occurrence of sensorineural hearing loss (44.4% of the cases) (26) . Upon comparing the subjects with HIV/AIDS submitted and not submitted to antiretroviral therapy, the data observed in the present study showed that there were no differences in occurrence of hearing loss in these two groups, confirming the results of some specific studies in the area (14,19,20) , and disagreeing with other studies that correlated the use of antiretroviral medication with higher occurrence of hearing impairment (5,9,(15)(16)(17)(18)21) . Considering the data found in the present study, we could observe that sensorineural hearing loss was associated with the presence of HIV virus and its adverse effects in the infected subject, in agreement with other studies published in the literature (10)(11)(12)14,24,25) .…”
Section: Discussioncontrasting
confidence: 66%
“…It is important to emphasize that the existing abnormalities may occur due to the action of the virus upon the body, the immunosuppression and presence of opportunistic infections, as well as the action of antiretroviral medication and potentially ototoxic medication (5,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)24) . The specialized literature has shown widely diversified results concerning the occurrence of hearing loss in the population with HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the as the time before diagnosis lengthened, the severity of hearing impairment increased, shown by the high prevalence of sensorineural hearing loss (37.5%) ( Table 5). Another study (27) detected a high viral load in patients with otologic clinical manifestations, further indicating the association between hearing loss and the time of diagnosis. Most studies of HIV-infected individuals (children or adults) report a higher prevalence of ear infections in addition to auditory symptoms, such as buzzing and ear ache, especially in patients undergoing antiretroviral therapy (7,19,24,27,28) .…”
Section: Discussionmentioning
confidence: 89%